Pengaruh Tekanan Peran dan dan Profesionalisme Terhadap Kinerja Auditor - Muhammad, Irsyad; Pura, Rahman (Insan Cita Bongaya Research Journal, 2022)
Public demands for supervision and accountability for the use of funds for the implementation of government activities require BPK RI auditors to further improve their performance professionally in order to produce quality audit activities. This study aims to analyze the effect of role stress and professionalism on auditor performance. The sample as well as the respondent is the BPK RI Representative of North Maluku, amounting to 35 auditors. Methods of data collection using questionnaires and analytical techniques and using multiple regression. The results showed that role stress had no effect on auditor performance, while professionalism had a positive and significant effect on auditor performance.